Tingkat Academic Burnout Mahasiswa di Masa Pandemi COVID-19 - Sagita, Dony Darma; Meilyawati, Vriesthia (Universitas Nusantara PGRI Kediri, 2021)
This study aims to explain and describe the level of academic burnout of FKIP students during the COVID-19 pandemic. This quantitative study is further elaborated with a descriptive approach. The research takes sample of 307 from total 6.544 students from the Faculty of Teaching and Education which then are given questionnaire consisting of 34 items. Based on the reliability test results using the Cronbach alpha method, the coefficient on the academic burnout questionnaire was 0.876. This research uses descriptive statistical analysis along with categorization to perceive the rate of academic burnout on the Faculty of Teaching and Education students. The result shows that 100% of the Faculty of Teaching and Education students in Universitas Muhammadiyah Prof. DR. HAMKA are having low level of academic burnout. This study concludes the low level of academic burnout of FKIP students is supported by the low results of each sub-variables analysis that are the dimensions of academic burnout itself, namely exhaustion (76%), cynicism (63%), and inefficacy (61%). The study results also exhibit the factors that are affecting academic burnout level in the Faculty of Teaching and Education students, including: 1) workload, 2) control, 3) reward, 4) community, 5) fairness, 6) values, 7) demographic characteristics, 8) education level, 9) personality, 10) levels of hardiness, 11) locus of control, 12) coping styles, and 13) social support.